Processing and stability of jenipapo nectar subjected to different methods of preservation - Figueiredo, Raimundo W. de; Maia, Geraldo Arraes; Holanda, Luciano F. Frota de; Monteiro, José Carlos S. (Pesquisa Agropecuaria Brasileira, 2014)
The stability of jenipapo (Genipa americana L.) nectar was studied through chemical, physiochemical, microbiological and sensory analysis. Jenipapo fruits from Manguarape, CE, Brazil were used as raw material. Nectar was storage for 150 days and its preservation was studied at high (100ºC for 15 minutes) and low (-18°C) temperature and also with chemical preservatives. As expected, storage at low temperature resulted in improve stability of the nectar for the whole storage period and somewhat greater acceptance by the sensory panel, although there were no statistics differences at 1% level of significance.